2021
DOI: 10.3846/ijspm.2021.14337
|View full text |Cite
|
Sign up to set email alerts
|

Under Invoicing in the Residential Real Estate Market in Pakistan

Abstract: In this paper the meaning of “under invoicing in a real estate market” signifies that the market value of real property exceeds its record value appearing in government documentation. The purpose of this study is to identify the level of under invoicing and determine the factors that affect the under invoicing in real estate markets in Pakistan. We apply OLS and Extreme Bounds Analysis techniques to test our propositions. The statistical sample consists of 338 real estate contracts. We find that under invoicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Through web scraping, data on 3,526 houses in Faisalabad were collected from zameen.com and geocoded. These prices serve as approximations, typically 3-5 percent higher than actual transactions (Wahid et al, 2021). While the property listing data does not provide transactional history, it serves as a proxy for market prices (C. Wu et al, 2016).…”
Section: Data and Sourcesmentioning
confidence: 99%
“…Through web scraping, data on 3,526 houses in Faisalabad were collected from zameen.com and geocoded. These prices serve as approximations, typically 3-5 percent higher than actual transactions (Wahid et al, 2021). While the property listing data does not provide transactional history, it serves as a proxy for market prices (C. Wu et al, 2016).…”
Section: Data and Sourcesmentioning
confidence: 99%
“…Due to the manual nature of property valuation in the country, there is a huge gap in property's actual market value and price determined by the government authorities like the FBR and the Deputy Commissioner (DC) rate of the BoR [103][104][105]. A comparison of market value of the property determined from the online property portal Zameen 1 , FBR 2 , and DC rate 3 in 2022 is given in Figure 4.…”
Section: Financialmentioning
confidence: 99%
“…It is observed that there is a significant difference between "DC rates" and market prices of the properties. As DC rates are lower relative to the market price in different housing authorities, most transactions in real estate are based on DC rates [5] (Wahid et al, 2021). However, actual transaction prices are recorded as market prices.…”
Section: Pricing Efficiency Of Real Estate Propertymentioning
confidence: 99%
“…Finally, the government policy vis-à-vis low-interest-rate mortgages for residential real estate in Pakistan provides an incentive as well as an opportunity for mispricing. Inasmuch as mispricing is pervasive, it distorts the incidence of real estate taxes (Wahid et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%